Association of a high rate of glycolysis and the activity of the uncoupling of oxidation and phosphorylation in the blood cells of patients with late-stage knee osteoarthritis and the development of postoperative pain - E. B. Chetina; G. A. Markova; K. E. Glemba; M. A. Makarov (Современная ревматология, 2024)
Objective: to investigate the relationship between the expression of genes mediating cellular energy production and the development of chronic postoperative pain (CPP) after total knee arthroplasty (TKA) in patients with osteoarthritis (OA).Material and methods. Prior to TKA, the blood of 50 patients with stage III–IV knee OA and complaints of constant pain and joint dysfunction was analyzed. The control group consisted of 26 healthy individuals. Pain intensity was assessed using a visual analogue scale (VAS), a short BPI questionnaire and the WOMAC index, and the presence of neuropathic pain was assessed using the DN4 and PainDETECT questionnaires. The development of CPP was determined 3 and 6 months after TKA. Total RNA isolated from blood was used to determine the expression of PKM2, LDH, SDH, AMPKα, PDH, IDH, MDH and ATP synthase genes by real-time quantitative reverse transcriptase-polymerase chain reaction.Results and discussion. CPP ≥30 mm according to VAS was detected in 17 patients. Before TKA, the expression of all analyzed genes was significantly increased compared to that of the control group. However, there were no differences in clinical, pain-related and functional indicators in the analyzed group of patients with OA. Before surgery, patients who subsequently developed CPP had significantly higher expression of genes related to glycolysis (PKM2, LDH), Krebs cycle – KC (SDH) and master regulator of energy metabolism (AMPKα) than patients who were satisfied with the results of TKA. At the same time, no differences were found in the expression of PDH and other KC enzyme genes (IDH, MDH) and ATP synthase in patients with and without CPP.Conclusion. The development of CPP is associated with a higher rate of glycolysis and energy deficiency, presumably due to the higher uncoupling activity of oxidation and phosphorylation that can be observed before TKA.